COC compliance - accessible improvement in the quality of life - A L Tikhomirov (IP Berlin A.V., 2013)
This is a article of the modern progestine in COC, and its effects. The compliance of the hormonal contraceptive Midiana containing drospirenone is described. The use of this medicine enhances the use of hormonal contraception. It is considered the distinctive features of the medicine; reduction in the severity of side effects, benefit effects.